Populism’s Challenges on Party Politics and Electoral Systems—A Comparative Study of USA and European Countries - Song, Yufei (Transactions on Economics, Business and Management Research, 2024)
The backdrop of this research is the global resurgence of populism, which poses various challenges to the conventional practices of party politics, electoral systems and democratic principles, particularly in Western countries. The research’s theme is to examine the impact and challenges of populist movements on political parties and electoral politics through two case studies of the United States and European countries respectively. It first analyzes how populism rises under a state’s party politics and electoral system, then discusses how it affects and poses challenges to party politics and democratic political orders. Through the methodology of comparative analysis, the research found that plurality voting presidentialism represented by the USA encourages charismatic populism with an authoritarian tendency despite the structure of two-party politics and European countries’ mixed-member parliamentary system allows populist parties to rise through split-voting but not to easily dominate as the ruling party. The conclusion is that populism’ rise under universal suffrage democracy is inevitable regardless of party and electoral systems but the negative impacts can be restrained by suitable institutional designs and self-correcting mechanisms of political parties, thus including populism in democratic systems instead of viewing populism as naturally contradictory to constitutional democracy.